Speech Function in Marhata Sinamot Prewedding Ceremony of the Simalungun - Nurhasanah Purba; Amrin Saragih; Nurlela Nurlela (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The aims of this study is to find out the speech function strategy used in marhata sinamot and how is the realization in mood. This research uses a qualitative descriptive method and used speech function’s theory of Halliday and Matthiessen theory (2014) and Saragih (2014). The result of this study shows that there are 243 clauses of speech function in marhata sinamot, and found 3 there types of speech function used in Marhata Sinamot prawedding ceremony, namely Statement, Question, and Command. The dominant speech function is statement. The statements which are realized in the mood of declarative were highly used in Marhata Sinamot because the speakers in Marhata Sinamot succeed in opting for declarative clauses in expressing their gratitude each other in going to be a family. In addition, the different customary rules between both families make giving each other more information in this event. While the realization of speech function in Marhata sinamot are found 2 types. The first is congruent realization found 229 clauses or about 94.3 % and second is metaphorical realization found 14 clauses or about 5.7%, they are 4 clauses of statement are realized in interrogative mood and 10 clauses of statement are realized in imperative mood. And the methaporical clause appears in Marhata Sinamot is influence of age and social position in Simalungun culture.